Collagenous colitis: a retrospective study of clinical presentation and treatment in 163 patients. Issue 6 (December 1996) - Bohr, J; Tysk, C; Eriksson, S; Abrahamsson, H; Järnerot, G
Abstract : BACKGROUND: Data on collagenous colitis have been based on a limited number of patients. AIMS: To obtain more information on this disease from a register set up at Orebro Medical Center Hospital. PATIENTS AND METHODS: Twenty five Swedish hospitals have contributed to this patient register, which comprises 163 histopathologically verified cases. Clinical data were retrospectively analysed. RESULTS: Collagenous colitis followed a chronic intermittent course in most cases (85%) with a sudden onset in 42%. Symptoms were chronic watery diarrhoea, often nocturnal (27%), abdominal pain (41%), and weight loss (42%). Sixty six patients (40%) had one or more associated diseases. Routine laboratory data were mostly normal. The median age at diagnosis was 55 (range 16-86) years, but 25% of the patients were younger than 45 years. Seven patients died of unrelated diseases. The response rate for sulphasalazine was 59%, and 50% and 40% for mesalazine and olsalazine. Prednisolone was most effective with a response rate of 82%, but the required dose was often high and the effect was not sustained after withdrawal. Antibiotics were efficient in 63%. Cholestyramine and loperamide had response rates of 59% and 71% respectively. CONCLUSIONS: Collagenous colitis follows a chronic continuous course. Symptoms can be socially disabling, but the disease does not seem to have a malignant potential. A plan for the treatment of a newly diagnosed patient with collagenous colitis is proposed.